I have posted previously on a problem in a similar vein here: Limit evaluation: very tough question, cannot use L'hopitals rule

I believe this problem is very similar, but it has stumped me.

$$\lim_{x \to 0}\frac{1-\frac12 x^2 - \cos\left(\frac{x}{1-x^2}\right)}{x^4}$$

Really appreciate it if someone has some insight on this.This comes out to be indeterminate if one plugs in zero. Following the idea from the link above, I tried to recognize this as derivative evaluated at zero of a function, BUT I could not find the function, because I tried to make this all over x, so that means the function I would create would generate a rational type with x^3 on the bottom. I guess I should also try to look at some trig limit identities as well.

Hope someone out there can see how to navigate this problem.


  • $\begingroup$ You should use Taylor formula to solve these kind of limits. $\endgroup$ – Emanuele Paolini Jan 3 '14 at 5:44
  • $\begingroup$ Is there a typo in your problem? Perhaps $$\lim_{x \to 0}\frac{1-\frac12x^2 - \cos(\frac{x}{1-x^2})}{x^4} ?$$ $\endgroup$ – Stephen Montgomery-Smith Jan 3 '14 at 5:54
  • $\begingroup$ Yes, you are correct, I missed the 1/2 in front of x^2 $\endgroup$ – Palu Jan 3 '14 at 5:56
  • $\begingroup$ Hi,I am using the taylor cosine series expansion. $\endgroup$ – Palu Jan 3 '14 at 5:57
  • $\begingroup$ @user99279: You should edit your question rather than leaving the correction in the comments. $\endgroup$ – user21820 Jan 3 '14 at 5:58

Like what Emanuele said, asymptotic expansions are useful for this kind of limits, and in fact better than L'Hopital (which fails miserably for some limits):

$\frac{x}{1-x^2} \in x + x^3 + O(x^5) \to 0$ as $x \to 0$

[We keep the error term so that at the end we know the error of the final approximation.]

$\cos( \frac{x}{1-x^2} ) \in 1 - \frac{1}{2} ( \frac{x}{1-x^2} )^2 + \frac{1}{24} ( \frac{x}{1-x^2} )^4 + O( ( \frac{x}{1-x^2} )^6 ) \\ \subset 1 - \frac{1}{2} (x+x^3+O(x^5))^2 + \frac{1}{24} (x+x^3+O(x^5))^4 + O(x^6) \text{ as } x \to 0 \\ \subset 1 - \frac{1}{2} x^2 - \frac{23}{24} x^4 + O(x^6) \text{ as } x \to 0$

[We can make the substitution into the Taylor expansion only because the input to $\cos$ tends to 0.]

$\frac{ 1 - \frac{1}{2} x^2 - \cos( \frac{x}{1-x^2} ) }{ x^4 } \in \frac{ \frac{23}{24} x^4 + O(x^6) }{ x^4 } = \frac{23}{24} + O(x^2) \to \frac{23}{24}$ as $x \to 0$

But you must make sure you understand the meaning of the Big-O notation and when and why they can be used. To make it more concrete, you can in many cases find explicit constants for bounds instead of using Big-O notation. For example:

$1 - \frac{1}{2} x^2 + \frac{1}{24} x^4 - \frac{1}{720} x^6 \le cos(x) \le 1 - \frac{1}{2} x^2 + \frac{1}{24} x^4$ [obtained by repeated differentiation and Mean-value theorem]

$x + x^3 \le \frac{x}{1-x^2} \le x + x^3 + 2 x^5$ for sufficiently small $x \ge 0$

$x + x^3 \ge \frac{x}{1-x^2} \ge x + x^3 + 2 x^5$ for sufficiently small $x \le 0$

  • $\begingroup$ Can you please tell me where I can learn these methods of solving the limits. I have searched so much but couldn't find anywhere these things and many other like limit of a summation, Newton-Leibniz Formula, etc. $\endgroup$ – adesh mishra Nov 18 '19 at 14:15
  • $\begingroup$ @adeshmishra: You can take a look at some other posts linked from my profile under "Asymptotic expansions". It's actually very simple once you fully grasp all the Landau notations (not just Big-O notation). $\endgroup$ – user21820 Nov 18 '19 at 17:10

$\frac 1{1-x^2}=1+x^2+O(x^4)$ then $\frac x{1-x^2}=x+x^3+O(x^5)$ then $\cos\left(\frac x{1-x^2}\right)=1-\frac{x^2}{2}-x^4+\frac{x^4}{24}+O(x^5)=1-\frac{x^2}{2}-\frac{23x^4}{24}+O(x^5)$ the limit is $\frac{23}{24}$.


Just expand $\cos\left(\frac{x}{1-x^2}\right)$ using series expansion and simplify a bit

  • $\begingroup$ Ignore the terms which have the numerator greater than x^4 because that will become zero anyway $\endgroup$ – Aman May 30 '15 at 7:21

Let $t=\dfrac{x} {2(1-x^2)}$ to simplify typing. Note that $t\to 0$ and $t/x\to 1/2$ as $x\to 0$. The numerator can be rewritten as $$2\sin^2t-2\cdot\frac{x^2}{4}=2\left(\sin t-\frac {x} {2}\right)\left(\sin t+\frac{x}{2}\right)=2AB\text{ (say)} $$ Clearly we have $$\frac{B} {x} =\frac{1}{2}+\dfrac{\sin t}{t}\cdot\frac{t}{x}\to \frac {1}{2}+1\cdot\frac{1}{2}=1$$ as $x\to 0$. And $$\frac{A} {x^3}=\frac{\sin t-t}{t^3}\cdot\frac{t^3}{x^3}+\frac{1}{2}\cdot\frac{1}{1-x^2}\to-\frac{1}{6}\cdot\frac{1}{8}+\frac {1}{2}=\frac{23}{48}$$ Therefore the given expression tends to $23/24$ as $x\to 0$. In the above process we have used the standard limit $$\lim_{t\to 0}\frac{\sin t} {t} =1$$ and the limit $$\lim_{t\to 0}\frac {\sin t-t} {t^3}=-\frac{1}{6}$$ which is easily proved via a single application of L'Hospital's Rule or via Taylor series for $\sin t$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.